Dogs in the dead of night - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series, 2011)
Jack and Annie travel to a monastery in the Swiss Alps where, with the help of St. Bernard dogs and magic, they seek the second of four special objects necessary to break the spell on the wizard Merlin's beloved penguin, Penny.